TUJUAN PENDIDIKAN PERSPEKTIF HADIS NABI SAW - Zulkarnain, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2014)
Education in the view of society is cultural inheritance from generation to generation, and the view of the individual is self-development potential and capabilities. Then, what about the purpose of education in the view of Prophetic traditions? to answer these questions, this paper attempted to study it using tahliliy method that begins with exploring the process takhrij al-hadith, hadith validity, analysis and understanding the text of hadith. The conclusion of hadith about the purpose of education has been narrated by al-Bukhariy, Muslim, Abu Dawud , al-Tirmidziy and Ibn Majah with a valid sanad. The Hadith is instructive that the filofosofis, education aims for people to get to know him so that it can perform tasks on earth Caliphate properly. Therefore, with the knowledge one can easily work righteousness that can easily also deliver them to heaven Allah